Pharmacokinetics of nanoparticles: current knowledge, future directions and its implications in drug delivery - Muthukrishnan Haripriyaa; Krishnamurthy Suthindhiran (SpringerOpen, 2023)
Abstract Background Nanoparticles have emerged as a viable biological candidate with the possibility to be employed as drug carriers. They acquire high surface-to-volume ratios and unique physicochemical features such as biochemical, magnetic, optical, and electrical changes at the cellular, atomic, and molecular levels. This phenomenon has proven extensive utility for biomedical applications, as their biological activity has fewer adverse effects than traditional medications. Main body of the abstract The new spectrum of nanomaterials-nanomedicines-has accomplished disease management by detecting, restoring, and regeneration of damaged tissues. Therefore, designing appropriate nanomaterial-based drug delivery systems for final clinical evaluations requires accurate knowledge of pharmacokinetic factors relevant to the LADME in order to meet the required criteria (liberation, adsorption, distribution, metabolism, and elimination). To identify and predict the in vivo reaction of nanoparticles, a deeper understanding of the link between the physicochemical properties of nanomaterials and their contact with the body is necessary. This will allow a distinguished comparison of traditional medicines and nanoparticles. Short conclusion This review paper attempts to analyze the basic pharmacokinetic potential of nanoparticles in depth. Therefore, profiling the pharmacokinetic analysis will enable us to review the treatment outcome to overcome their adverse properties, provide a broad overview, and deliver remarkable ways to advance the use of nanoparticles in the biomedical industry. Graphical abstract